Subcellular platelet factor VIII antigen and von Willebrand factor (The Rockefeller University Press, 1975)
Subcellular membrane and granule fractions derived from human platelets contain factor VIIII antigen and von Willebrand factor activity but not factor VII procoagulant activity. Circulating platelets constitute a significant reservoir of plasma factor VIII antigen, containing approximately 15% of the amount of factor VIII antigen present in platelet-poor plasma. The antibiotic ristocetin, which aggregates human platelets in the presence of von Willebrand factor, nonspecifically precipitates platelet membrane factor VIII antigen. Thus normal platelets contain surface-bound as well as internally stored von Willebrand factor, a protein synthesized by endothelial cells which is necessary for normal platelet function in vivo.